Small molecules from cycloaddition reactions: synthesis, theoretical perspectives, and biological evaluation - Tallarida, Matteo Antonio; Maiuolo, Loredana; Catalano, Stefania; Breugst, Martin; Rutjes, Floris (Università della Calabria, 2023)
The research work is related to a Ph.D. course in Translational Medicine of the Department of Pharmacy, Health, and Nutritional Sciences, University of Calabria. The project was carried out at the Department of Chemistry and Chemical Technologies of the same institution under the supervision of Prof. Loredana Maiuolo in the Laboratory of Organic Synthesis and Chemical Preparations (LabOrSy) headed by Prof. Antonio De Nino. The main subject of this research regards the use of cycloaddition reactions for the synthesis of small molecules with potential biological activity in diverse contexts. Alongside the prominent synthetic part, a series of QM computational studies were conducted to clarify some reaction mechanisms. In addition, molecular docking studies were performed to propose potential targets for some of the prepared compounds. The work is subdivided into four main parts. The first chapter is dedicated to the synthesis of 1,5-disubstituted 1,2,3-triazoles, to a series of molecular docking simulations, and to the biological evaluation of two compounds as inhibitors of the permeability transition pore opening event. The second part is about the microwave-assisted synthesis of isoxazolidine bisphosphonates as potential farnesyl pyrophosphate synthase (hFPPS) inhibitors. The third chapter focuses on the use of pyridinium ylides as building blocks for the multicomponent synthesis of indolizines and spirocyclopropyl oxindoles. The reaction mechanism regarding these latter was computationally investigated. The fourth – and last – chapter regards the synthesis and the radical expansion reaction of norbornane derivatives. A computational assessment of the mechanism is reported also in this case. All the computational studies reported in chapters 1, 3, and 4 were conducted in the frame of an abroad research stay spent in the Computational Chemistry Group headed by Dr. Gonzalo Jiménez Osés of the Center for Cooperative Research in Biosciences (CIC bioGUNE).
Università della Calabria. Dipartimento di Farmacia e scienze della salute e della nutrizione. Dottorato di ricerca in Medicina Traslazionale. Ciclo XXXV
Keywords: Small Molecules; Cycloaddition Reactions; Click chemistry; DFT calculations; Molecular Docking